Sikap dan Pemahaman Masyarakat Desa Nirannuang Kecamatan Bontomarannu Terhadap Arah Kiblat Sebagai Kesempurnaan Ibadah - Fachrul Salam Baharuddin; Rahmatiah,HL; Muh. Saleh Ridwan (Universitas Islam Negeri Alauddin Makassar, 2023)
The main problem in this study is how are the attitudes and understanding of the community regarding the Qibla direction, especially the people who are in Nirannuang Village, Bontomarannu District, Gowa Regency. This research is classified as a simple quantitative research type with a syar'i approach and a social approach. This research uses population and sample. The population taken is the people of Nirannuang Village and the sample is 30 people from 9 mosques. Furthermore, the data collection method used in this study is observation, closed interviews with instruments that have been prepared by researchers, and documentation. The results of this study indicate that the attitude of the people of Nirannuang Village towards the Qibla direction is quite good, the majority of respondents who the researchers took as a sample assume that the Qibla direction is the direction of the Kaaba, so when praying they must face the Kaaba as a form of obedience in carrying out obligatory prayers or sunnah. Meanwhile, the understanding of the people of Nirannuang Village towards the Qibla direction is still lacking. This is because the majority of respondents understand how important knowledge of the Qibla direction is, but there are still many people who think that the Qibla direction is west. Keywords: Attitude, Understanding,Qibla Direction and Nirannuang Village